1992
DOI: 10.1152/ajpgi.1992.262.4.g740
|View full text |Cite
|
Sign up to set email alerts
|

Role of cholecystokinin in induction and maintenance of dietary protein-stimulated pancreatic growth

Abstract: The role of cholecystokinin (CCK) in induction and maintenance of pancreatic growth stimulated by a high-protein diet was investigated. Rats adapted to 5% casein diet were switched to 70% casein for 21 days. MK-329, a CCK receptor antagonist, was administered at 2.5 mg.kg-1.day-1 ip, beginning on day zero (day zero treatment) or day 7 (midcourse treatment) of feeding 70% casein and thereafter. Another group was returned to 5% casein after 7 days of feeding 70% casein. Feeding 70% casein significantly stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…It is believed that oral administration of protease inhibitor or dietary protein induces release of endogenous CCK, resulting in stimulation of pancreatic growth (17,18). To confirm the role of endogenous CCK in the pancreatic growth induced by camostat, we fed camostat to CCK-deficient mice for 10 days.…”
Section: Effect Of Camostat On Pancreatic Growth In Micementioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that oral administration of protease inhibitor or dietary protein induces release of endogenous CCK, resulting in stimulation of pancreatic growth (17,18). To confirm the role of endogenous CCK in the pancreatic growth induced by camostat, we fed camostat to CCK-deficient mice for 10 days.…”
Section: Effect Of Camostat On Pancreatic Growth In Micementioning
confidence: 99%
“…It is well known that feeding initiates pancreatic protein synthesis and secretion and that adaptation to a high-protein diet results in pancreatic growth (17,18). More detailed studies have shown that among gastrointestinal peptides, CCK is released in response to dietary protein leading to pancreatic growth.…”
mentioning
confidence: 99%
“…Although some experiments utilizing pharmacological CCK receptor antagonists in rats seemed to support this hypothesis (14,25), it has been demonstrated that rats fed high concentrations of amino acids, which unlike protein do not stimulate CCK secretion (21), have significant pancreatic hypertrophy (18). More definitively, Lacourse et al (20) generated a CCK-deficient mouse and demonstrated that pancreatic hypertrophy resulting from feeding a protein-enriched diet is similar in CCK-deficient mice and wild-type littermates.…”
mentioning
confidence: 99%
“…Switching from a 5-10% casein diet to one containing 70-75% casein caused an increase in pancreatic weight, protein and DNA content reaching a plateau in 7-14 days (40,41,91). This was accompanied by a transient increase in plasma CCK and the growth response could be partially blocked with a CCK antagonist (41,91).…”
Section: High Protein Dietmentioning
confidence: 97%
“…Until recently the most common technique was dissecting and weighing the pancreas. This yields values for young adults, usually males, fed a control diet, of 8-12 mg pancreatic weight/g body weight for mice (22,64,120,125,143), 22.5 mg PW/gBW for Syrian Hamster (124), 2.5-4 mg PW/g BW for rats (25,34,40,57,123,158), and 0.5-1.1 g PW/kg BW for adult humans (13,127). Note that the relative pancreas size gets smaller as the animal gets larger.…”
Section: Measurement Of Pancreatic Sizementioning
confidence: 99%